Matrix‐assisted laser desorption/ionisation (MALDI) TOF analysis identifies serum angiotensin II concentrations as a strong predictor of all‐cause and breast cancer (BCa)‐specific mortality following breast surgery. Issue 10 (4th June 2015) - Boccardo, Francesco; Rubagotti, Alessandra; Nuzzo, Pier Vitale; Argellati, Francesca; Savarino, Grazia; Romano, Paolo; Damonte, Gianluca; Rocco, Mattia; Profumo, Aldo
<x xml:space="preserve">Abstract</x> MALDI‐TOF MS was used to recognise serum peptidome profiles predictive of mortality in women affected by early BCa. Mortality was analysed based on signal profiling, and appropriate statistics were used. The results indicate that four signals were increased in deceased patients compared with living patients. Three of the four signals were individually associated with all‐cause mortality, but only one having mass/charge ratio (m/z) 1, 046.49 was associated with BCa‐specific mortality and was the only peak to maintain an independent prognostic role after multivariate analysis. Two groups exhibiting different mortality probabilities were identified after clustering patients based on the expression of the four peptides, but m/z 1, 046.49 was exclusively expressed in the cluster exhibiting the worst mortality outcome, thus confirming the crucial value of this peptide. The specific role of this peak was confirmed by competing risk analysis. MS findings were validated by ELISA analysis after demonstrating that m/z 1, 046.49 structurally corresponded to Angiotensin II (ATII). In fact, mortality results obtained after arbitrarily dividing patients according to an ATII serum value of 255 pg/ml (which corresponds to the 66th percentile value) were approximately comparable to those previously demonstrated when the same patients were analysed according to the expression of signal m/z 1, 046.49. Similarly, ATII levels were specifically correlated with BCa‐related deaths after competing risk analysis. In conclusion, ATII levels were increased in women who exhibited worse mortality outcomes, reinforcing the evidence that this peptide potentially significantly affects the natural history of early BCa. Our findings also confirm that MALDI‐TOF MS is an efficient screening tool to identify novel tumour markers and that MS findings can be rapidly validated through less complex techniques, such as ELISA.